Soil organic carbon and total nitrogen in a Leucaena leucocephala silvopastoral system in the Chaco region, Argentina - Banegas, Natalia Romina (2025)
The introduction of leucaena (Leucaena leucocephala) in silvopastoral systems increases animal production and improves soil fertility. However, there is limited information on the dynamics of carbon and nitrogen in these systems over the long-term periods and soil profile. This study compared the concentrations and vertical distribution of organic carbon (OC) and total nitrogen (TN), and its fractions (particulate and associated forms) in the soil profile (0-100 cm), with and without leucaena, 10 years after its establishment in a tropical pasture (Urochloa brizantha-Chloris gayana). Leucaena increased OC by 73% in the deeper horizon (50-100 cm), particularly in its stable form. It also increased TN by 12% in the surface layer (0-20 cm) and by 21% in the deeper horizon. These increases in OC and TN with leucaena can be associated to root biomass allocation deeper into the soil profile, increased N inputs from leaf deposition, animal manure and urine, and nodule N-fixation. Despite the rise in TN in the surface soil, OC decreased in this layer, which is linked to the low grass cover, a result of high grazing pressure aimed at controlling leucaena hedgerow height. Under proper grazing management, leucaena has the potential to improve soil fertility and nitrogen availability for companion grasses, and may also serve as a greenhouse gas mitigation strategy.